Trickery and buffoonery as subversion re-viewing Juan Pusong in a postcolonial context - Dimzon, Eliodora L. (Danyag :the UPV journal of humanities and social sciences, 2005)
"This article attempts to offer some insights to the study of local folklore by offering a new way of looking at Juan Pusong, a famous central character in West Visayan trickster and numskull tales. Through a postcolonial reading of ten tales involving him or his representation, recurring motifs of subversion are identified and these do not only highlight forms of resistance to the ruling class/colonial power but also stir and challenge some western norms."